Inhibition of albendazole and 2‐(2‐aminophenyl)‐1H‐benzimidazole against tyrosinase: mechanism, structure–activity relationship, and anti‐browning effect. (27th January 2023) - Wen, Yiting; Zhang, Yujia; Zhang, Xiaoli; Wang, Linjun; Pan, Qiuxia; Bai, Qiuhan; Zhu, Du; Chai, Weiming
Abstract: BACKGROUND: Tyrosinase is the key enzyme involved in enzymatic browning of plant‐derived foods. Inhibition of tyrosinase activity contributes to the control of food browning. Due to safety regulations or other issues, most identified tyrosinase inhibitors are not suitable for practical use. Therefore, it is necessary to search for novel tyrosinase inhibitors. In this study, the anti‐tyrosinase activity and mechanism of albendazole and 2‐(2‐aminophenyl)‐1 H ‐benzimidazole (2‐2‐A‐1HB) were investigated through ultraviolet–visible absorption spectroscopy, fluorescence spectra, molecular docking, and molecular dynamic (MD) simulation. The anti‐browning effect of albendazole on fresh‐cut apples was then elucidated. RESULTS: Albendazole and 2‐2‐A‐1HB were both efficient tyrosinase inhibitors with IC50 of 51 ± 1.5 and 128 ± 1.3 μmol L −1, respectively. Albendazole suppressed tyrosinase non‐competitively and formed tyrosinase–albendazole complex statically. Hydrogen bond and hydrophobic interaction were major driving forces in stabilizing the tyrosinase–albendazole complex. While 2‐2‐A‐1HB inhibited the enzyme competitively and quenched its intrinsic fluorescence through a static mechanism, it generated strong binding affinity with tyrosinase through hydrophobic interaction. MD simulations further validated that albendazole/2‐2‐A‐1HB could form stable complexes with tyrosinase and loosened its basic framework structure, leading to a change in secondary structure and conformation. In addition, albendazole could delay the browning of fresh‐cut apples by inhibiting the activity of polyphenol oxidase, peroxidase and phenylalanine ammonia‐lyase, and reducing the oxidation of phenolic compounds. CONCLUSION: This research might provide a deep view of tyrosinase inhibition by benzimidazole derivatives and a theoretical basis for developing albendazole as a potential fresh‐keeping agent. © 2023 Society of Chemical Industry.